PENGARUH KOMPOSISI BAHAN BAKU SECARA STOIKIOMETRI DAN NON STOIKIOMETRI TERHADAP SIFAT FISIS DAN MAGNET PADA PEMBUATAN MAGNET PERMANEN BaO.6Fe2O3 - kharismayanti Ritonga (Saintia Fisika, 2013)
ABSTRACTWe have made hard magnetic Barium Heksaferit from BaCO3 and Fe2O3 technical with varying composition of BaCO3 and Fe2O3 in Stoichiometric ratio (1:6) and Non Stoichiometric ratio (1:6,5). Preparation process by wet mixing and grinding by using Plenatery Ball Milling (PBM) and dried, The testing of Analyze Temperature Differential (DTA) to determine the calcination temperature. The powder then calcined at 10000C and held for 2 hours. Subsequently analyzed using X-Ray Diffractometer (XRD) and the results indicate that the structure has been formed BaO.6Fe2O3. The powder was then sieved to pass 400 mesh (38μm) by adding 3 %wt seluna as adhesives. Printing was done using a magnetic anisotropy field press and pressurized at 5 tons. Then sintered with temperature 11500C, and held for 2 hours. Characterization includes: XRD analysis, flux density measurements with a gaussmeter, measure the density, porosity, BaO.6Fe2O3 morphology with SEM andmeasurement BH curve with permagraf. From the research that has a magnetic Barium Heksaferit the highest magnetic field strength magnets are made with Non-Stoichiometric, is 506,3 Gauss, density = 3,9 g/cm3, porosity = 5,96%, shrinkage = 21.37%, Remanensi (Br) = 1,27 kG, Coercivity (HcJ) = 3,88 kOe, Energy product (BH max) = 0.36 MGOe.Key Word : Hard Megnetic, BaO.6Fe2O3, Stoichiometric and Non stoichiometric ratio, density, BH curve.